KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA : LITERATURE REVIEW - Herindraningrum, Farah Faadillah; Yuhertiana, Indrawati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This literature review aims to map research on the quality of local government financial reports in Indonesia and to see how the role of accountability and transparency factors in the quality of local government reports in Indonesia. This research method uses SLR (Systematic Literature Review). Analysis of data by mapping 28 selected journals from 2015 to 2020 in the Google Scholar database. The results of this research show factors affecting the quality of the Indonesian government's financial reports, namely: human resource competence, Information Technology, Accountability, Transportation, Audit Quality, Accounting System, Accounting Procedure, Accounting Standards, and Internal Management with quantitative research type, Qualitative, literature review, and mix method. The most frequently investigated factor is the competence of human resources as much as 15 times the type of research that is widely used is quantitative research as much as 20. This research also shows that the accountability and transparency of financial reporting have a significant effect on the quality of financial reporting of local governments in Indonesia.